Understanding relationship between physical quality indicators and organic carbon in soils affected by long-time continuous cultivation under sub-humid ecosystem - Deividas Mikstas; Orhan Dengiz (Eurasian Journal of Soil Science, 2023)
The objectives of this present study were to analyses soils and find out some soil quality properties and check relationship between soil compaction, crust formation and erodibility - K of the soils with the soil organic carbon (SOC) amount in the surface (0-20 cm) and subsurface (20-40 cm) soils affected by long-time continuous cultivation under sub-humid environmental condition. The research out comes showed that soil compaction, crust formation, erodibility K is highly significantly (P < 0.001) related to organic carbon, organic carbon stock, organic matter and between each other. The research also identifies that the study area generally, has clay texture, neutral pH, low amount of the CaCO3, high amount of OC and OM in top layer (0-20 cm) and moderate amount in bottom layer (20-40 cm). It was not identified significant differences between the soil properties in surface and subsurface soil layers.